Age, gender, and religiosity as related to death anxiety - Chan, Li Chuin *; Yap, Chin Choo * (Sunway University College, 2009)
Western society has always been somewhat intrigued by death anxiety and its causes. In comparison, the study of death anxiety has not been given much importance in other cultures. Due to this, some interesting questions have risen such as: does death anxiety exist in other cultures? Do the same variables that seem to attenuate death anxiety in Western countries function as well for individuals in other cultures? Thus, the purpose of this study was to examine the influence of religion, religious orientation, gender, and age on death anxiety in a culturally diverse country like Malaysia. There were 320 participants ranging in age from 17-70 years who took part in the study. It was hypothesized that a) participants with an affiliation to a religion would have lower death anxiety, b)a negative relationship between intrinsic religious orientation and death anxiety, and a positive relationship between extrinsic religious orientation and death anxiety would exist, c) female participants would have lower death anxiety, and d) death anxiety levels would not differ between young adults and older adults. A survey method was used in this study and participants were required to complete the Templer Death Anxiety Scale (TDAS) as well as the Age Universal Religious Orientation Scale. The results supported hypothesis c) and d). No significant negative relationship existed between intrinsic religious orientation and death anxiety, and no significant positive relationship existed between extrinsic religious orientation and death anxiety. Further research and implications are discussed.